POTENSI PENGGUNAAN SMARTWATCH SEBAGAI ALAT PEMBERI UMPAN BALIK RESUSITASI JANTUNG PARU: SEBUAH KAJIAN SISTEMATIS - Dirjayanto, Valerie Josephine; Soloan, Garry; Duindrahajeng, Bernadine Gracia (JIMKI: Jurnal Ilmiah Mahasiswa Kedokteran Indonesia, 2023)
Introduction: Cardiac arrest is the first cause of mortality, causing 50% of all cardiovascular deaths. Previous studies have documented the potency of electronic devices such as smartwatch in increasing the quality of cardiopulmonary resuscitation (CPR). Thus, this review is made in order to evaluate the utility of smartwatches in increasing the quality of various CPR parameters. Methods: This review follows PRISMA guidelines, searching for studies from databases such as PubMed, Cochrane, Science Direct, Wiley Online Library, Scopus, and Google Scholar that evaluate the utility of smartwatches in increasing parameters of CPR quality, including depth or frequency, in adults and pediatric population. Quality of studies are assessed with Revised Cochrane Risk of Bias Tool for Randomized Trials (RoB) 2.0. Results and Discussion: Smartwatches are proven effective in guiding CPR both during in-hospital cardiac arrest (IHCA) and more so in out-of-hospital cardiac arrest (OHCA). Smartwatch can increase both the accuracy of frequency and depth of chest compressions significantly. In pediatric population, regardless of expertise of helper, smartwatches can help in achieving high quality CPR. Feedback feature from smartwatches can prevent over- and underventilation. With increase of confidence of helper in reducing patient injury, smartwatch is also potential for maintaining CPR quality, resulting in better patient survival. Conclusion: This review shows the effectiveness of smartwatches as CPR feedback devices that can increase quality, both in terms of depth and frequency. Further clinical studies are encouraged with greater samples to strengthen evidence.